2022
DOI: 10.1371/journal.pone.0269804
|View full text |Cite
|
Sign up to set email alerts
|

Rate of diagnosed seasonal influenza in children with influenza-like illness: A cross-sectional study

Abstract: Introduction Although influenza surveillance systems have been used to monitor influenza epidemics, these systems generally evaluate diagnostic information obtained from medical institutions and they do not include patients who have not been examined. In contrast, community based epidemiological studies target people with influenza-like illness (ILI) that self-reported influenza-like symptoms whether they have medical examinations or not. Because the criteria for influenza surveillance systems and ILI differ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Boca virus was positive in one school aged child (1%), adeno virus in 5 children (1 preschool and 3 school aged and 2 adolescents - 5.1%) and rhino virus in 1 child (preschool age, 1%). Notably, this is comparable to a pre covid Japanese study by Mitsuo et al which revealed 70.2% of ILI in school aged children in their season of influenza [ 9 ]. The present study also depicts that, 78.5% cases of ILI are due to influenza viruses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Boca virus was positive in one school aged child (1%), adeno virus in 5 children (1 preschool and 3 school aged and 2 adolescents - 5.1%) and rhino virus in 1 child (preschool age, 1%). Notably, this is comparable to a pre covid Japanese study by Mitsuo et al which revealed 70.2% of ILI in school aged children in their season of influenza [ 9 ]. The present study also depicts that, 78.5% cases of ILI are due to influenza viruses.…”
Section: Discussionsupporting
confidence: 86%
“…this is comparable to a pre covid Japanese study by Mitsuo et al which revealed 70.2% of ILI in school aged children in their season of influenza[9]. The present study also depicts that, 78.5% cases of ILI are due to influenza viruses.…”
supporting
confidence: 90%
“…In addition, influenza vaccination was demonstrated to improve school attendance and children wellbeing (18). Children with ILI generally do not seek medical care, and not all ILI affected subjects are included in influenza surveillance systems (19). School-based surveillance can represent a valid option, but medical staff need to be present within the building to record symptoms and collect samples.…”
Section: Introductionmentioning
confidence: 99%